Gestational Diabetes Mellitus Among Asians – A Systematic Review From a Population Health Perspective - Li, Ling-Jun; Huang, Lihua; Tobias, Deirdre K.; Zhang, Cuilin (Frontiers in Endocrinology, 2022)
Objective: Since Asians are particularly vulnerable to the risk of gestational diabetes mellitus (GDM), the lifecourse health implications of which are far beyond pregnancy, we aimed to summarize the literature to understand the research gaps on current GDM research among Asians. Methods: We systematically searched the articles in PubMed, Web of Science, Embase, and Scopus by 30 June 2021 with keywords applied on three topics, namely “GDM prevalence in Asians”, “GDM and maternal health outcomes in Asians”, and “GDM and offspring health outcomes in Asians”. Results: We observed that Asian women (natives and immigrants) are at the highest risk of developing GDM and subsequent progression to type 2 diabetes among all populations. Children born to GDM-complicated pregnancies had a higher risk of macrosomia and congenital anomalies (i.e. heart, kidney and urinary tract) at birth and greater adiposity later in life. Conclusion: This review summarized various determinants underlying the conversion between GDM and long-term health outcomes in Asian women, and it might shed light on efforts to prevent GDM and improve the lifecourse health in Asians from a public health perspective.